An Analysis of the Hell – Heaven Paradigm in Thai Society - Sutthisilo (Masawanna), Phra Maha Lampai; PhrakruSripanyavikrom; Suvaco, Phramaha Phocana (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study the philosophical paradigm, 2) to study the paradigm of hell-heaven in Thai society, and 3) to analyze the paradigm of hell-heaven in Thai society. This research is a qualitative research, with methods of collecting and analyzing data from documents, textbooks, academic articles, and related research, both primary and secondary. The research results found that: 1. Philosophical paradigms refer to a system of beliefs or fundamental assumptions about the nature of existence and the world. It serves as a foundation for humans to view the world and the things around them, guiding their thought processes and actions in life. Philosophical paradigms aim to propose ideas on development, paradigm shifts, and philosophical paradigms for human development. As times change, old paradigms must be re-examined and updated to align with the present and future circumstances. A new paradigm can emerge only when the existing paradigm is no longer effective in solving problems or responding to human development. 2. The study of hell and heaven in Thai society found that the concepts of hell and heaven in Thai society are viewed from multiple dimensions, such as the realms or planes of existence and sensory faculties (āyatanas). Belief in these concepts often manifests as faith and devotion, leading to the creation of religious literature, such as the Mahāchat Kham Luang, Vessantara Jātaka, Phra Mālai Kham Luang, and various Jātaka tales. Additionally, belief in deities, spirits, or sacred beings is also present in many Thai literary works, such as the Traibhumikathā (the Three Worlds), which discusses Hell and Heaven. These beliefs reflect the influence of Buddhism in Thai society, where the promotion of generosity and charity serves as a means to attain heaven. However, as Thai society evolved and scientific knowledge from the Western world began to infiltrate contemporary thought, traditional beliefs have been reinterpreted to fit the modern era. 3. An analysis of the paradigms of hell and heaven in Thai society through a philosophical concepts found that the understanding of beliefs serves as a foundational way of perceiving the world and reality. Paradigms change according to time and place, and they can transcend limitations to help ensure human existence. Thai ancestors embraced Buddhism as a guiding practice since Sukhothai kingdom, continuing through Lanna Kingdom, Ayutthaya kingdom, and Rattanakosin kingdom respectively, making Buddhism deeply intertwined with Thai society. Thai adopted Buddhist principles as a guiding framework for life, which became ingrained in cultural practices and traditions. These traditions are so integrated that it would be nearly impossible to separate Buddhism from Thai society.